2019
DOI: 10.17263/jlls.547683
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of difficulties in second language writing

Abstract: Among the four language skills, writing is considered as the most challenging and difficult skill for most of the foreign language learners (Reid, 2002). Moreover, the development of students' L2 writing can be influenced by multiple factors such as L1 writing ability, L2 proficiency, and writing experiences in both languages (Kobayashi & Rinnert, 2008; Kubota, 1998). The starting point of this study was the difficulties students face in their writing process observed during the in-class writing tasks (Kobayas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 8 publications
4
16
4
Order By: Relevance
“…The perceived difficulties in writing of the student-respondents also represent the challenges discovered in other empirical studies. In other words, the difficulties in writing revealed in this study were also seen in previous empirical works such as in the research of Ismail (2010), Cai (2013), Al Badi (2015), Alhojailan (2015), Ibnian (2017), Al Mubarak (2017), Alkubaidi (2017), Al Tamimi (2018), Jabali (2018), Lalam (2018), Pablo and Lasten (2018), Ariyanti and Fitriana (2018), Ceylan (2019), and Al Mukdad (2019). These difficulties in writing range from the structural to organization difficulties.…”
Section: Discussionsupporting
confidence: 87%
“…The perceived difficulties in writing of the student-respondents also represent the challenges discovered in other empirical studies. In other words, the difficulties in writing revealed in this study were also seen in previous empirical works such as in the research of Ismail (2010), Cai (2013), Al Badi (2015), Alhojailan (2015), Ibnian (2017), Al Mubarak (2017), Alkubaidi (2017), Al Tamimi (2018), Jabali (2018), Lalam (2018), Pablo and Lasten (2018), Ariyanti and Fitriana (2018), Ceylan (2019), and Al Mukdad (2019). These difficulties in writing range from the structural to organization difficulties.…”
Section: Discussionsupporting
confidence: 87%
“…Also, students at the tertiary level experienced various obstacles in their processes of writing. The obstacles derive from many aspects as the foregone researches such as vocabulary and diction (Meslissorgou & Frantzi, 2015;Nugraheni & Basya, 2018;Toba et al, 2019;Zhan, 2015), grammatical features (Ariyanti & Fitriana, 2017;Hajeid, 2018;Hasan & Marzuki, 2017;Meslissorgou & Frantzi, 2015;Nugraheni & Basya, 2018;Toba et al, 2019;Zhan, 2015), exploring and generating ideas (Asadifard & Koosha, 2013;Ceylan, 2019;Hosseini et al, 2013;Nugraheni & Basya, 2018), organization (Hajeid, 2018;Nugraheni & Basya, 2018;Toba et al, 2019), and teaching process (Ceylan, 2019;Hajeid, 2018;Jebreil et al, 2015). Accordingly, the aforementioned studies have shown that the major difficulties found in students' writing are mostly in the areas of vocabulary and grammar.…”
Section: Writing Difficultiesmentioning
confidence: 99%
“…In an academic setting, enhancing writing skills for the students is the primary objective in education (Al Khazraji, 2019). For students to develop their writing competence, they are expected to produce a well-structured piece of writing (Ceylan, 2019). Moreover, mastering how to organize, regulate writing behavior, review the composition, and provide readers awareness (Bakry & Alsamadani, 2015) have also become the crucial aspect for creating a well-produced piece of writing.…”
Section: Introductionmentioning
confidence: 99%
“…It is the physical act of committing words or ideas to some medium, whether it is an object or a symbol or an email message. Evidently many studies have found that students encounter many difficulties in the process of making a writing (Fareed et al, 2016;Okumuş, 2019;Siddiqui, 2020). The difficulty is found in the lack of students' ability to develop ideas, grammar and the ability to compose coherence sentences.…”
Section: Introductionmentioning
confidence: 99%